Analysis of Community E-commerce Marketing Strategies—Taking Meituan Youxuan as an Example - Lei Mei; Yuning Cao (Theoretical Hypotheses and Empirical Results, 2025)
This article aims to optimize Meituan Youxuans marketing strategies, continuously seek new growth points, and enhance its core competitiveness. It analyzes the issues present in Meituan Youxuans marketing process and proposes corresponding solutions to optimize its future development, thereby helping Meituan Youxuan build a moat in an increasingly competitive market. By integrating the 4C theory and SWOT analysis theory, this study delves into Meituan Youxuans marketing strategies from aspects such as its development background, market positioning, and business performance. It identifies problems in the marketing strategy and proposes specific optimization plans to address these issues, aiming to improve the existing problems in Meituan Youxuans marketing strategy.